2021
DOI: 10.1002/jemt.23900
|View full text |Cite
|
Sign up to set email alerts
|

Modulating response of sunflower (Hellianthus annuus) to induced salinity stress through application of engineered urea functionalized hydroxyapatite nanoparticles

Abstract: Agro-nanotechnology aims to improve the quality and quantity of plants and plant products while preserving environmental health. Contemporary anecdotal studies that provide representation of the use of nanostructures as fertilizers, pesticides, and plant growth regulators have highlighted the need to determine the effect of such modified nanofertilizers on transforming plant yield under abiotic stress. Present study was performed to modulate the physiological response of Hellianthus annuus through the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 48 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Similarly, our results revealed a prompt decline in photosynthetic pigments, i.e., chlorophyll a, b, and carotenoids, under the influence of Pb stress. Previous studies suggested that plant lead exposure shows lessening in photosynthetic activity due to CO 2 deficiency resulting from stomatal closure, restrained chlorophyll and carotenoid synthesis, deformation of the chloroplast ultra-structure, obstruction of the thylakoid electron transport system, and impairment with enzymes associated with the Calvin cycle [63]. Pb causes alterations in glycolipids, specifically affecting monogalactosyldiacylglycerol, which is closely linked to changes in chloroplast membrane permeability [60].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our results revealed a prompt decline in photosynthetic pigments, i.e., chlorophyll a, b, and carotenoids, under the influence of Pb stress. Previous studies suggested that plant lead exposure shows lessening in photosynthetic activity due to CO 2 deficiency resulting from stomatal closure, restrained chlorophyll and carotenoid synthesis, deformation of the chloroplast ultra-structure, obstruction of the thylakoid electron transport system, and impairment with enzymes associated with the Calvin cycle [63]. Pb causes alterations in glycolipids, specifically affecting monogalactosyldiacylglycerol, which is closely linked to changes in chloroplast membrane permeability [60].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of new types of bioceramics has been highlighted due to their importance in the medical field (Cintra et al, 2022). Among various forms of bioceramics, the hydroxyapatite, Ca 10 (PO4) 6 (OH) 2 or HAP (Bulajic et al, 2022) has more interest from many researchers due to their excellent osteointegrative, good biocompatibility, and excellent osteoconductive performance (Dorozhkin, 2009; Ullah et al, 2022; Wang & Yeung, 2017). HAP has a high ability to interact with proteins because of charged oxygen ions and the positively charged calcium ions (Ca 2+ ) associated with phosphate anions (PnormalO43) that interact electrostatically with side groups of proteins, as well as by the chelation of calcium ions of the HAP with electron donor amino acids of proteins (Coutinho et al, 2020; Fiume et al, 2021).…”
Section: Introductionmentioning
confidence: 99%